2021
DOI: 10.17843/rpmesp.2021.382.7158
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados a la muerte por COVID-19 en pacientes admitidos en un hospital público en Tacna, Perú

Abstract: Objetivo: Describir las características demográficas, clínicas, laboratoriales y de tratamiento de pacientes hospitalizados por la COVID-19 y determinar los factores de riesgo de mortalidad hospitalaria. Materiales y métodos: Estudio de cohorte retrospectivo de pacientes adultos hospitalizados por la COVID-19. Se extrajeron datos demográficos, clínicos, laboratoriales y de tratamiento de las historias clínicas de pacientes que ingresaron al Hospital III Daniel Alcides Carrión de Tacna. Para el análisis de supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
10
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 16 publications
9
10
0
18
Order By: Relevance
“…Our cohort showed a high mortality rate (46%) like other Peruvian hospital cohorts [ 5 8 , 10 , 11 ] which reported a mortality between 33% and 50%. Peru is the third country in Latin America with the highest mortality beneath Brazil and Mexico [ 12 ].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our cohort showed a high mortality rate (46%) like other Peruvian hospital cohorts [ 5 8 , 10 , 11 ] which reported a mortality between 33% and 50%. Peru is the third country in Latin America with the highest mortality beneath Brazil and Mexico [ 12 ].…”
Section: Discussionsupporting
confidence: 57%
“…Within the group of hospitalized patients, mortality can be close to 50% [ 7 ], which can be even higher in older patients, those with comorbidities or with a lower oxygen saturation (SaO 2 ) at admission [ 5 , 6 ]. Among laboratory markers, C-reactive protein (CRP), procalcitonin, lactate dehydrogenase (LDH) and platelets, among others, could predict a serious clinical deterioration in these patients [ 8 10 ]. However, predictors of mortality are heterogeneous among different countries.…”
Section: Introductionmentioning
confidence: 99%
“…This difference is particularly relevant due to the high rate of carbapenem resistance of A. baumannii and Pseudomonas aeruginosa in this cohort, which was 96% and 100%. This high proportion of multidrug-resistant microorganisms could be due to the almost universal consumption of antibiotics in our cohort (99%), well above that described by other authors (64-72%) [22][23][24], and to the deviation from adequate infection prevention and control practices, probably related to the collapse of the Peruvian health system [20].…”
Section: Discussionsupporting
confidence: 85%
“…The mortality found in this study (33%) is similar to that reported for ICU patients in other hospitals [12,[18][19][20]. Although most of these reports are from high-income countries, patients with critical COVID-19 in our hospital were governed by constantly updated protocols as new evidence appeared, which probably impacted mortality.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, the possible benefit of NTZ has been argued in several studies [44,45] and more recently, the combined use of NTZ, ivermectin, ribavirin, and zinc supplement effectively cleared the SARS-COV2 from the nasopharynx in a shorter time than symptomatic therapy [46]. There are studies with contradictory information on colchicine, some encouraging its use [47,48] and others leaving a doubt on its effectiveness [49,50].…”
Section: Discussionmentioning
confidence: 99%